Merekabentuk Dan Membina Penukar Buck Dc Ke Dc Dengan Sistem Kawalan Gegelung Suap Balik - Ismail, Khairudin (Universiti Sains Malaysia, 2006)
The project of design and construction of dc – dc buck converter with feedback loop control system is not a new design in use of application with many electronic apparatus nowadays. This project used feedback loop control system as a controller as a circuit that control the smooth flow of conducted current and voltage. This project used an integrated circuit model NCP 1501 as dc switching controller circuit and produced by ON Semiconductor. This IC is built from a few smaller circuit that been internally built inside IC and it shows that buck converter operation I/O system are within the IC itself. The system used inside this project save money and give benefits particularly to user because of cheap cost of the component. For simulation, we use software called OrCAD 9.0 where simulation of waveform of input and output voltage and current conducted in the circuit. This software can provide schematic diagram and output waveform of our choice. Many researches have been done in order for better understanding about dc buck converter. Hopefully this report helps you to explain more about the design ands construction of dc – dc buck converter using feed back loop control system.